THE EFFECT OF CORPORATE EARNINGS MANAGEMENT AGAINST BOND RATING AT FINANCIAL INSTITUTIONS ISLAMIC BANKING FINANCIAL INSTITUTIONS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2022 - Sutisnawati, Yayah; Hakim, Luqman; Andini, Raysha (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to analysis the effect of earnings management on bond ratings in Islamic banking financial institutions listed on the Indonesia Stock Exchange during the period 2018-2022. Earnings management is the independent variable while bond rating is the dependent variable. Through descriptive methods and simple linear regression analysis, the development of the effect of earnings management on bond ratings was observed. The results of data analysis show that the t value for the effect of earnings management on bond rating is 3.414 with a significance value of 0.002. Comparison between t count and t table shows that t count is greater than t table (3.414 > 2.048) and the significance value is less than 0.05. Thus, at 5% error rate, the decision to reject Ho and accept Ha is taken. In conclusion, earnings management has a significant influence on bond ratings at Islamic banking financial institutions in Indonesia.